A Comparative Study of Effect of Rhizobium and PGPR Alongwith Sulphur and Micronutrients on the Protein Content of Blackgram and Lentil Respectively: Impact of Rhizobium and PGPR with Sulphur and Micronutrients on Protein Content (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A field experiment was conducted at the research farm of J. V. College Baraut, Baghpat, blackgram seeds were first inoculated with Rhizobium and that of lentil with PGPR. Sulphur was used in the form of gypsum (60 kgha), Zn in the form of zinc sulphate (4 kgha), Mo as sodium molybdate (0.1 kgha), B. as borax (0.6 kgha) and Mn as manganese sulphate (0.5kgha) in different basal dosage with different combinations. Combined treatment of Rhizobium with sulphur and micronutrients significantly increased the protein content in black gram over any other treatment. Likewise combined treatment of PGPR with sulphur and micronutrients significantly increased the protein content in lentil over any other treatment. comparatively both Rhizobium and PGPR with sulphur and micronutrients have almost equal effect on protein content of both the crop but effect of Rhizobium in blackgram was more pronounced than that of PGPR in lentil (in term of increase in protein content).